2019
DOI: 10.1111/jcmm.14359
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA SNHG6 promotes cell proliferation and migration through sponging miR‐4465 in ovarian clear cell carcinoma

Abstract: Dysregulation of small nucleolar RNA host gene 6 (SNHG6) exerts critical oncogenic effects and facilitates tumourigenesis in human cancers. However, little information about the expression pattern of SNHG6 in ovarian clear cell carcinoma (OCCC) is available, and the contributions of this long non‐coding RNA to the tumourigenesis and progression of OCCC are unclear. In the present study, we showed via quantitative real‐time PCR that SNHG6 expression was abnormally up‐regulated in OCCC tissues relative to that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…overexpressed SNHG6 reduces cell apoptosis but promotes cell cycle, cell migration, invasion, EMT, and chemoresistance. SNHG6 exerts its function mainly by serving as miRNA sponge to antagonize the connections between multiple tumor suppressor miRNAs and their target mRNAs [19][20][21][22][23] . In this study, we analyzed public database and found that SNHG6 was also upregulated in CCA cell lines and tissues, and functional investigations showed that SNHG6 silencing inhibited cell proliferation, migration, and HUVECs tube formation, which indicated that SNHG6 functioned as an oncogene in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…overexpressed SNHG6 reduces cell apoptosis but promotes cell cycle, cell migration, invasion, EMT, and chemoresistance. SNHG6 exerts its function mainly by serving as miRNA sponge to antagonize the connections between multiple tumor suppressor miRNAs and their target mRNAs [19][20][21][22][23] . In this study, we analyzed public database and found that SNHG6 was also upregulated in CCA cell lines and tissues, and functional investigations showed that SNHG6 silencing inhibited cell proliferation, migration, and HUVECs tube formation, which indicated that SNHG6 functioned as an oncogene in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the regulatory mechanisms of SNHG6 are mediated by sponging a variety of miRNAs . SNHG6 also acts as a competing endogenous RNA to upregulate E2F7 by sponging miR‐26a‐5p in LUAD .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SNHG6 acts as the sponges of microRNAs (miRNAs) to participate in the pathogenesis of multiple malignancies. Accumulating evidence shows that SNHG6 acts as an oncogenic factor by sponging miR‐4465 in ovarian clear cell carcinoma and miR‐181a‐5p/−miR‐26a/b/−214 in CRC . These studies indicate that SNHG6 can mediate miRNA networks to participate in cancer progression.…”
Section: Introductionmentioning
confidence: 88%
“…All of the included studies were performed in China and were published from 2016 to 2019 with a mean sample size of 71. In terms of the type of cancer, 5 studies referred to colorectal cancer [10][11][12][13][14], 2 studies related to glioma [15,26], 2 studies involved osteosarcoma [16,27], and the remaining cohorts were on ovarian cancer [18], lung cancer [19], oesophageal cancer [20], gastric cancer [21], and liver cancer [22]. Of the 14 studies included, 6 had survival dates in the original literature, and the survival dates for the others were determined with graphical survival plots following the published method proposed by Tierney et al [28].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…With the development of high-throughput RNA sequencing techniques and bioinformatic algorithms, a spectrum of lncRNAs have been identified. The small nucleolar RNA host gene 6 (SNHG6; also termed U87HG), a subclass of lncRNA molecules, pervasively participates in gene modulation through functioning as an oncogene in different human cancers, including colorectal cancer [10][11][12][13][14], glioma [15], osteosarcoma [16], breast cancer [17], ovarian cancer [18], lung adenocarcinoma [19], oesophageal cancer [20], gastric cancer [21] and liver cancer [22]. Studies have proven that the upregulation of SNHG6 plays multiple critical roles in cell differentiation, proliferation, apoptosis, and multidrug resistance [23,24].…”
Section: Introductionmentioning
confidence: 99%